Pengaruh Return On Equity, Debt To Equity Ratio, Return On Asset Dan Cash Ratio Terhadap Harga Saham - Sofyan, Frama Aditya; Norisanti, Nor; Sunarya, Erry (Peneliti.net, 2023)
The research was aimed at determining the influence of Return On Equity towards Stock Price, the influence of Debt To Equity Ratio towards Stock Price, the influence of Return On Asset towards Stock Price, the influence of Cash ratio towards Stock Price on companies in cosmetics and household goods sector listed in the Indonesia Stock Exchange (IDX) for the period of 2016-2021. The objects of the research were Return On Equity (X1), Debt To Equity Ratio (X2), Return On Asset (X3), Cash Ratio (X4), and Stock Price (Y). The research methods applied were descriptive and associative with quantitative approach. Samples used in the research were 5 out of 11 samples, taken by Purposive Sampling technique. The techniques of analysing data conducted were correlation analysis, coefficient of termination analysis, multiple linear regression, research model testing (F-test), and research hypothesis testing (T-test), while SPSS 26 was used for tabulating data. The results of the research show that there is a relationship of Return On Equity, Debt To Equity Ratio, Return On Asset, and Cash Ratio towards Stock Price which is aggregated to 0.982, indicating that the relationship of Return On Equity, Debt To Equity Ratio, Return On Asset, and Cash Ratio towards Stock Price is included to a very strong relationship criteria. Meanwhile, partially, Return On Equity (ROE) influences negatively and insignificantly towards Stock Price; partially, Debt To Equity Ratio (DER) influences positively and significantly towards Stock Price; partially, Return On Asset (ROA) influences negatively and insignificantly towards Stock Price; partially, Cash Ratio (CR) influences positively and significantly towards Stock Price.